Bioequivalence study of generic acyclovir compared with the brand name acyclovir - Rojanasthien N. (2014)
The bioequivalence study of 200-mg generic acyclovir was conducted in healthy males. The reference Zovirax and the test Zevin were administered as a single oral dose after an overnight fast in a two-period, crossover design separated by 1 week. Serial blood samples were collected over a period of 24 hours. Plasma acyclovir concentrations were determined by HPLC and the pharmacokinetic parameters were analyzed by non-compartmental analysis. RESULTS: The t 1/2 for the test (4.5 +/- 2.4 h) and Zoviraxl (3.9 +/- 2.6 h) were comparable. The analysis of variance was carried out and the median Tmax (1.50 h) for the test was not statistically difference from Zovirax. The mean (90% CI) of the AUC0-infinity and the Cmax ratios for (Test/reference) were 0.95 (0.83-1.09) and 0.95 (0.83-1.10), respectively. These values fell within the bioequivalence criteria of 0.80-1.25, thus it was concluded that Zevin and Zovirax were bioequivalence.